2018
DOI: 10.7150/ijms.22713
|View full text |Cite
|
Sign up to set email alerts
|

Propofol attenuates osteoclastogenesis by lowering RANKL/OPG ratio in mouse osteoblasts

Abstract: Bone remodeling plays an important role in the bone healing process; for example, following fracture. The relative ratio of the receptor activator of nuclear factor kappa B ligand (RANKL)/ osteoprotegerin (OPG) controls osteoclast differentiation, thereby playing a pivotal role in the regulation of bone remodeling. Propofol, a widely used anesthetic agent in orthopedic procedures, is considered to possess potential antioxidant properties owing to its structural similarity to α-tocopherol. Antioxidants are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…Under homeostatic conditions, RANKL and OPG expression are balanced. The relative proportion of RANKL/OPG controls the differentiation of osteoclasts, thus playing a central role in the regulation of bone remodeling 50. The RANKL/OPG ratio observed in our study, especially for ES-stimulated groups, favorably modulated the bone remodeling process, which was also demonstrated by TRAP-positive cells.…”
supporting
confidence: 57%
“…Under homeostatic conditions, RANKL and OPG expression are balanced. The relative proportion of RANKL/OPG controls the differentiation of osteoclasts, thus playing a central role in the regulation of bone remodeling 50. The RANKL/OPG ratio observed in our study, especially for ES-stimulated groups, favorably modulated the bone remodeling process, which was also demonstrated by TRAP-positive cells.…”
supporting
confidence: 57%
“…This result was also verified by immunofluorescence analysis, suggesting that there may be interactions between the bone/bone marrow microenvironment and prostate cancer cells in vivo. Although we found that hBMSC and hFOB1.19 cells also enhanced the expression of OPG in PC3 cells, activation or inhibition of the RANK/-RANKL signaling pathway depends on the ratio of RANKL to OPG in the microenvironment [38,39], i.e., if the increase in RANKL expression is greater than that of OPG, the RANK/RANKL signaling pathway will still be activated. Thus, an increase in OPG expression and the activation of the RANK/RANKL signaling pathway are not necessarily contradictory.…”
Section: Biomed Research Internationalmentioning
confidence: 58%
“…In addition, osteoblasts mainly synthesize oteoprotegerin (OPG) as a circulating decoy receptor of RANKL [61]. The soluble RANKL/OPG system controls the differentiation and function of osteoclasts, thereby clinically determining bone status [62]. Growing evidence suggests that epigenetic modification plays a critical role in the formation of normal bone and the pathogenesis of bone diseases [63].…”
Section: Discussionmentioning
confidence: 99%